Tentang PPN PMSE Indonesia: Masih Ada yang Perlu Diperbaiki? - Wulandari, Destiny (Politeknik Keuangan Negara STAN, 2023)
This study aims to find out a concept behind e-commerce VAT enactment and dig review materials to be a guidance to improve the existing e-commerce VAT collection system in Indonesia. This study uses narrative literature review on 20 international literatures regarding e-commerce VAT in digital economy era. The results conclude that there is nothing wrong with the e-commerce VAT enactment on digital transaction although there are some challenges ahead. The e-commerce VAT collection system that involves e-commerce business actors as the VAT collectors is a common system. To prevent a higher collection cost, VAT can be imposed on all types of transaction either business-to-business transactions or business-to-consumer transactions and on all types of goods and services either the low-value ones or not. Establishing adequate monitoring system, creating strict law enforcement rules, and making a detailed e-commerce VAT collection guidance are several efforts that can be done to improve e-commerce VAT collection system in Indonesia.